Impact of Factors Associated with the Academic Achievement of Continuing Education Students in Peru - Puertas, Mónica Aurora (2025)
Objective. Analyze the impact of teaching modality, age, and gender on the academic achievement of continuing education students in the Peruvian context. Methodology. The research is descriptive with a quantitative approach. Data from 436 students of a diploma course taught in face-to-face (2018-2019) and online (2020-2022) modalities were analyzed. Statistical tests such as analysis of variance (ANOVA) and Student’s t were used to assess the impact of independent variables on academic achievement. Results. ANOVA showed a significant impact of teaching mode (η²p = 0.128) and a small impact of age (η²p = 0.017), but not of gender. The t-tests showed a higher average performance in the virtual mode compared to the face-to-face mode, with a moderate effect size (d = 0.77). In terms of age, no significant differences were found within each modality, although the younger group performed better in the online modality. Discussion and conclusions. The online modality can offer advantages for continuing education in the context of this research, possibly because of its flexibility and adaptation to the profile of adult learners. It is also suggested to take into account the influence of these factors in the adoption of pedagogical strategies for the planning of continuing education activities, as well as to promote a competent, equitable, and quality educational environment, considering its constant improvement and evaluation.